Dynamic transmission models and economic evaluations of pneumococcal conjugate vaccines: a quality appraisal and limitations. (October 2021) - Løchen, Alessandra; Anderson, Roy M.
Abstract: Background: Of over 90 serotypes of Streptococcus pneumoniae, only 7 were included in the first pneumococcal conjugate vaccine (PCV). While PCV reduced the disease incidence, in part because of a herd immunity effect, a replacement effect was observed whereby disease was increasingly caused by serotypes not included in the vaccine. Dynamic transmission models can account for these effects to describe post-vaccination scenarios, whereas economic evaluations can enable decision-makers to compare vaccines of increasing valency for implementation. Objective: The aim of this review was to examine epidemiological and economic models and their assumptions for their potential contributions to future research and immunisation policy. Sources: Pubmed, Scopus, Ovid, ISI Web of Knowledge, Centre of Reviews and Dissemination (CRD) databases were searched. Content: Twenty-three dynamic transmission models and twenty-one economic models were retrieved and reviewed. Published models employed various templates, revealing several key uncertainties regarding the biology and epidemiology of pneumococcal infection. While models suggested that PCVs will reduce the burden of disease, the extent to which they are predicted to do so depended on various assumptions regarding features of pneumococcal infection and epidemiology that governed PCV cost-effectiveness as well. Such features include the duration of protection and competitive interactions between serotypes, which are unclear at present, but which directly relate to herd immunity and serotype replacement. Implications: Economic evaluations are not typically based on transmission dynamic models and hence omit indirect herd immunity effects. The two tools could be used in conjunction to inform decision-makers on vaccine implementation, but so far there have been few attempts to build economic evaluations on transmission dynamic models, and none in this field. Future directions for research could include studies to evaluate key parameters for the models involving herd immunity, serotype competition and the natural history of infection.